Untangling the Maze of European Union Funds to Bulgaria - Vincelette, Gallina Andronova; Vassileva, Iglika (World Bank, Washington, DC, 2012)
The paper presents a fiscal estimate of Bulgaria's perspective European Union (EU) membership. The projected EU funds have two distinct effects: first, there is the overall effect on the balance of payments of the country; and second, there is the pure effect on the national budget. The paper concludes that Bulgaria is likely to benefit from large net inflows of resources of an average of 3.7 percent of gross domestic product (GDP) in 2007-09. In contrast, its fiscal position is expected to deteriorate by 1.6 percent of GDP on average in 2007-09 if no expenditure restructuring of the fiscal framework is carried out. The expected deterioration of the public finances related to EU accession would be due to co-financing requirements, national contributions to the EU budget, and possible full pre-financing of the EU direct payments to Bulgarian farmers in the first year of accession. However, the above expenditures will be partly offset by the budgetary compensation allocated out of the EU budget, savings from agricultural subsidies, and shifting of certain public expenditures to Cohesion Fund-supported projects.